Successful Endoscopic Ultrasound-Guided Transduodenal Biliary Drainage Through a Pre-Existing Duodenal Stent - Belletrutti, Paul J; Gerdes, Hans; Schattner, Mark A (JOP. Journal of the Pancreas, 2010)
Context When ERCP fails in the setting of combined biliary and duodenal obstruction, EUS-guided biliary drainage has emerged as an alternate method of biliary decompression. Case report We present a case of a 40-year-old man with advanced pancreatic cancer and a pre-existing duodenal wall stent who subsequently develops jaundice due to biliary obstruction. An ERCP was technically unsuccessful as the papilla was inaccessible despite probing within the duodenal stent. Transduodenal biliary drainage was achieved using EUS guidance to create a choledochoduodenostomy tract. A fully covered metal biliary stent was then deployed through the mesh of the duodenal wall stent. The patient’s jaundice and pruritus subsequently resolved. Conclusion This is the first report of successful transduodenal EUS-guided biliary drainage performed through an existing enteral wall stent and can still be considered as an alternate mode of biliary drainage in this setting. Image: Deployed metal biliary stent protruding through mesh of duodenal wall stent.